Cultural Insights from To Kill a Mockingbird: Understanding Racial Prejudice and Social Justice in Educational Literature Course - Marliana, Rina; Ramli, Rahmi (Jurnal Pendidikan Bahasa Inggris undiksha, 2025)
This research explores the impact of To Kill a Mockingbird by Harper Lee on undergraduate students’ cultural understanding, focusing on themes of racial prejudice, empathy, moral development, and social justice. Using Focus Group Discussions (FGD) as the primary data collection method, the study gathered insights from 30 students enrolled in an educational literature course, English Education Study Program STAIN Majene. The findings revealed that the novel significantly enhanced students’ awareness of racial inequalities, prompting them to draw connections between the novel’s historical context and modern-day issues such as systemic racism and social justice movements like Black Lives Matter. The study also highlighted the novel's role in fostering empathy and emotional engagement, particularly through the character development of Scout Finch and her moral growth. Furthermore, the novel encouraged students to reflect on their own cultural biases, leading to increased self-awareness and a commitment to addressing social inequalities. The research emphasizes the ongoing relevance of To Kill a Mockingbird in contemporary education, demonstrating its ability to promote critical thinking, moral courage, and cultural empathy. The study suggests that literature plays a vital role in addressing societal issues and fostering a more inclusive, socially conscious generation